(untitled) (Stamford Journal of Microbiology, 2020)
Due to delicious taste and readily availability, desserts are one of the most popular foods in Dhaka city. High amount of carbohydrate and protein in dessert items make them more susceptible to proliferation of microbial growth. Present study depicted a complete microbiological profile of some popular desserts such as, sweet, pastry, ice cream, pudding, falooda, yogurt and custard available in different food shop at Dhaka city, Bangladesh. All the samples were found to be contaminated with heterotrophic bacteria as well as fungi within the range of 103 to 106 cfu/g. In case of specific microflora, the growth of Staphylococcus spp., Klebsiella spp. and Pseudomonas spp. were observed in most of the samples indicates the poor quality of these products. Bioburdens of E. coli in sweet, pudding and yogurt were found in the range of 1.2×102 to 2.7×103 cfu/g. Salmonella spp., Shigella spp. and Vibrio spp. could not be isolated from any of the samples. Current study indicates that hygienic conditions should be maintained during preparation, packaging and retailing of dessert items in order to reduce the load of contamination in ready to eat foods which will ensure good health of consumers. Stamford Journal of Microbiology, Vol.9(1) 2019: 19-22